A Regulatory Framework for Islamic Banks - Ismail, A. G.; Sanusi, N. A. (Universiti Sains Islam Malaysia, 2024)
This paper seeks to provide a framework for addressing regulatory issues which impact operations and institutional development of Islamic banks. Arguing against universal regulation or creating separate specialized regulations, the approach in this paper uses the regulatory dialectic principle to highlight the need to regulate Islamic banks and focuses on the area of regulations that need to be covered and regulated. The area of regulations can be classified into seven broad categories, i.e regulations on bank activities, bank entry, capital adequacy, deposit insurance, monitoring, government ownership and supervision. The area of regulations providing stability in a financial system context cannot develop without a conducive legal and regulatory environment. Finally, we will introduce the CAMEL rating to measure the soundness of Islamic banks.